Agent-based design for fault management system in industrial processes - Cerrada, Mariela; Aguilar, José; Cardillo, Juan; Faneite, Raúl (Rev. Téc. Fac. Ing. Univ. Zulia)
Al the present time, the necessities of the industry demand procedures for global management, integrating information systems to manipulate and to use the information in the controlled processes. These considerations lead to the development of supports systems for decisions-making, for which fault detection and diagnostic system are vital aspects. In this work, a multi-agent-based reference model for fault management in industrial processes is proposed. The fault management problem is viewed like a feedback control process and the actions are related to the decision-making in the scheduling of the preventive maintenance task and the running of preventive and corrective specific maintenance tasks. A particular methodology allowing the conception and analysis of the agent systems is used for the agents design. As a result, a set of models describing the general characteristics of the agents, specific tasks, communications and coordination is obtained.